Mystery of the dark magic : starring Doctor Strange - Snider, Brandon T. (Mighty Marvel chapter book., 2019)
"When the Avengers battle of werelizards that mysteriously appear at a Long Island mall, they call the best in the magic business to help them out--Doctor Strange. But the good doctor is overworked and underpaid. These days he's become the go-to hero for all things magical, and he's exhausted. He'd really prefer to work alone, since it's not like anyone can understand his mastery of the mystic arts. As more bizarre attacks occur around New York City, Strange finds himself seeking guidance from a number of mystical allies. But when the sinister beastlings grow wildly beyond his control, can Doctor Strange accept the counsel of his super hero comrades in order to save his best friend and the world?--Back cover.